PENGARUH PERBANDINGAN MEDIUM TOPSOIL DENGAN EFFLUENT DAN PEMBERIAN PUPUK NPK PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Vika Nurhasanah; Wardati '; Islan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this research was to determine the effect ofmedium comparison (Topsoil : Effluent) and get the best dose giving NPK fertilizer on oil palm seedling at main nursery. This research was conducted at the experimental station of Agriculture Faculty, University of Riau on April 2015 until July 2015. This research was arranged on using Completely Rendomized Design (CDR) with two factorial: Factor 1;medium comparison , E0 (10kgTopsoil : 0 kg Effluent), E1 (9 kg Topsoil : 1 kg Effluent), E2 (8 kg Topsoil : 2 kg Effluent), E3 (7 kg Topsoil : 3 kg Effluent), E4 (6 kg Topsoil : 4 kg Effluent). Factor II; N0 (NPK 5 g/polybag), N1( NPK 10 g/polybag), N2 (NPK 15 g/polybag) and replicated 3 times, so abtained 45 unit experiment. Parameter observed were the accretion of plant heigh, accretion of stump diameter, accretion of leaves number, root shoot ratio and dry weight. The result showed that medium comparison(Topsoil : Effluent) and giving NPK fertilizer interaction effect on accretion of leaves number, but not significantly on accretion of plant heigh, accretionof stump diameter, root shoot ratio and dry weight. The best result shows on 6 kg Topsoil : 4 kg Effluent and NPK 15 g /polybag.Effluent treatment on oil palm seedling effect to all parameters, whereas on the NPK giving effect to all parameters except the accretionof stump diameter and root shoot ratio. Keywords : Oil palm seedling, Effluent, NPK